Playing Music May Improve the Gait Pattern in Patients with Bilateral Caloric Areflexia Wearing a Cochlear Implant: Results from a Pilot Study - Hallemans, Ann; Mertens, Griet; Van de Heyning, Paul; Van Rompaey, Vincent (Frontiers in Neurology, 2017)
Hypothesis: Auditory information through an active cochlear implant influences gait parameters in adults with bilateral vestibular lossbilateral caloric areflexia and profound sensorineural hearing loss. Background: Patients with bilateral vestibular lossbilateral caloric areflexia suffer from imbalance, resulting in an increased risk of falling. In case of simultaneous deafness, the lack of auditory feedback results in less awareness of the auditory scene. This combination might produce significant challenges while walking and navigating. Auditory cues can be restored to some extent with a cochlear implant (CI). Electrical stimulation through a CI can also produce a vestibulo-collic reflex through current spread which can be measured as cervical vestibular-evoked myogenic potentials. Methods: Adults (7 males, 1 female, mean age 61 ± 14 years), wearing a cochlear implant to treat profound sensorineural hearing loss and presenting with bilateral vestibular lossbilateral caloric areflexia walked barefoot, over ground, at self-selected speed in three different conditions: with cochlear implant turned on, while listening to music and with cochlear implant turned off. Spatiotemporal and kinematic parameters of gait were calculated using the conventional gait model. Results: Removing auditory feedback by turning off the cochlear implant decreased stride time (mean difference 0.0.03s ± 0.0.15s) and slightly increased stride length (mean difference 0.5 ± 1.2 cm) compared to the control condition with the cochlear implant on. Walking while playing music positively affected gait compared to walking with the cochlear implant on but without auditory feedback. By increasing the motion of the pelvis (mean difference 1.3° ± 0.4°), the knee (mean difference 3.9° ± 0.8°) and the ankle (mean difference 2.2° ± 0.2°), stride length increased (7.8 ± 1.2 cm), while stride time decreased (0.059s ± 0.016s). Conclusions: Although a practice effect cannot be completely ruled out, this pilot study suggests that playing music while wearing an active cochlear implant may improve gait in patients with bilateral otovestibular loss. It remains unclear if the musical cues boost balance control or the cochlear implant might produce current spread and electrical stimulation to the vestibular afferents, thereby boosting its detection threshold, through stochastic resonance, and improving gait.